A narrative approach to helping an adult with a mild learning disability to confront "the gremlin". (18th May 2018) - Lewis, Vicky; Rose, David
Abstract : Accessible summary: Sometimes people with a learning disability find things hard which changes how they think, feel and what they do. The psychology team supports people with feelings, thoughts, relationships and behaviours. Narrative therapy is a way of helping people to understand things in a different way. Narrative therapy assumes that people have many skills and are good at lots of things which can help them to reduce the impact of what they find hard. This is the story of how I helped a woman with a learning disability using narrative therapy. It is important to share this story so that narrative therapy can be used to help other people. Abstract: Background: The main assumption of narrative therapy is that people are the "experts" on their own lives. When working with people with a learning disability, it can often be the case that the client's voice is not the primary voice. This is due to the fact that others "hold" the story for the client. When the story is, therefore, told, it is done so from the perspective of that person. Narrative therapy has been found to provide an opportunity to access the perspective and experience of those whose voice may otherwise be excluded. Materials and Methods: This paper details a case study which explains how a woman with a mild learning disability was helped to confront overwhelming anxiety which she referred to as "the gremlin." The client described how "the gremlin" was having an influence over her ability to manage in stressful situations and cope with change. A narrative approach was utilised which focussed on reducing the influence of "the gremlin." Results: The client's evaluation of the therapy using self‐report and scaling measures showed that it had been a success. The client identified times where stories other than the dominant were lived and she became the primary author of preferred stories of her life, reducing the influence of "the gremlin." Conclusions: This study described how narrative therapy helped a woman with a learning disability and provides an example for use with other clients in the future.